The Use of English Narratives in Promoting Banggai Coastal Culture Through Cultural Tourism - Lampadjoa, Faradifa Sudirman; Laya, Agustian; Akbar, Filla; Sabbu, Sukma Widya Sasmi (IKIP Siliwangi, 2026)
Tourism serves not only as an economic driver but also as a medium for preserving and transmitting cultural identity. In Banggai, Central Sulawesi, coastal traditions and rituals such as Molabot Tumpe and lobe fishing embody rich local wisdom with strong potential for cultural tourism. However, linguistic limitations and inconsistent English representation have hindered effective promotion at the global level. This study explores how English narratives are constructed and utilized to promote Banggai’s coastal culture. A qualitative descriptive approach was employed, involving semi-structured interviews with three key informants: a cultural expert, a tour guide, and a tourism practitioner, supported by document analysis of brochures, websites, social media content, and promotional videos. Data were analyzed thematically and through discourse analysis to examine diction, narrative style, and structure. The results identify five dominant forms of English narratives: comparison, descriptive-promotional, personal invitation, experiential-practical, and cultural awareness. These narratives effectively convey ceremonial, culinary, and social aspects of Banggai’s culture but underrepresent expressive heritage such as songs, dances, and oral storytelling. The findings also reveal challenges in linguistic competence, cultural translation, and stakeholder collaboration. Overall, the study highlights that English narratives act as cultural mediators that enhance Banggai’s visibility, authenticity, and sustainability in global tourism. By emphasizing narrative competence and intercultural collaboration, this research contributes to developing English-for-Tourism practices that support both cultural preservation and destination branding.